Carbon pump: Fundamental theory and applications. (15th January 2017) - Zhao, Ruikai; Deng, Shuai; Liu, Yinan; Zhao, Qing; He, Junnan; Zhao, Li
Abstract: Currently, significant energy consumption is one of the main technical barriers to the large-scale application of CO2 capture technology. A novel concept—carbon pump—is proposed in this paper to analyze the energy-efficiency of these technologies. The analysis model, which embodies the carbon pump concept, includes the minimum CO2 separation work and the second-law efficiency. Based on this model, the proposed method is applied to comparative analysis of current capture technologies considering both the quantity of energy consumption and the grade of difficulty level for CO2 separation. The analyzed results show that the second-law efficiencies of the statistical cases are below 35%. For post-combustion technologies with CO2 concentrations ranging from 5% to 15%, the higher group of second-law efficiency is approximately above 15%, and the lower is approximately 10% or lower. It can be concluded that a great energy-saving potential still exists in post-combustion technologies through improving the efficiency of heat exchanger and pump, developing new materials, and network optimization. Additionally, integrating renewable energy into capture technologies is an important measure for reducing the consumption of primary energy and the carbon footprint of the whole system. Graphical abstract: Highlights: Introduction of carbon pump model analogous to heat pump or water pump. Evaluation/comparison of second-law efficiency of current CO2 capture technologies. Strategies of reducing energy consumption for CO2 capture by renewable energy.